Ecophysiological response to seasonal variations in water availability in the arborescent, endemic plant Vellozia gigantea - Morales, M.; Garcia, Q. S.; Munne-Bosch, S. (Tree physiology, 2015)
The physiological response of plants growing in their natural habitat is strongly determined by seasonal variations in environmental conditions and the interaction of abiotic and biotic stresses. Here, leaf water and nutrient contents, changes in cellular redox state and endogenous levels of stress-related phytohormones (abscisic acid (ABA), salicylic acid and jasmonates) were examined during the rainy and dry season in Vellozia gigantea, an endemic species growing at high elevations in the rupestrian fields of the Espinhaço Range in Brazil. Enhanced stomatal closure and increased ABA levels during the dry season were associated with an efficient control of leaf water content. Moreover, reductions in 12-oxo-phytodienoic acid (OPDA) levels during the dry season were observed, while levels of other jasmonates, such as jasmonic acid and jasmonoyl-isoleucine, were not affected. Changes in ABA and OPDA levels correlated with endogenous concentrations of iron and silicon, hydrogen peroxide, and vitamin E, thus indicating complex interactions between water and nutrient contents, changes in cellular redox state and endogenous hormone concentrations. Results also suggested crosstalk between activation of mechanisms for drought stress tolerance (as mediated by ABA) and biotic stress resistance (mediated by jasmonates), in which vitamin E levels may serve as a control point. It is concluded that, aside from a tight ABA-associated regulation of stomatal closure during the dry season, crosstalk between activation of abiotic and biotic defences, and nutrient accumulation in leaves may be important modulators of plant stress responses in plants growing in their natural habitat.